Survival Rate, Biomechanical Complications, and Patient Satisfaction of Implant-Supported FRC Full-Arch Prostheses: A Retrospective Study with Follow up of 5 Years - Daniel Hernández-González; Mauro Marincola; Antonio Diaz-Caballero; Alfredo Passaretti; Andrea Cicconetti (Shiraz University of Medical Sciences, 2024)
Statement of the Problem: The satisfaction of patients with dentures on implants has different points of view that become fundamental aspects for the development of research on the quality of life of these patients, the eventual biomechanical complications to which these prostheses and implants can be subjected, and design considerations for cantilever extensions.Purpose: The objective of research was to assess the implants and prosthesis survival rates, biomechanical complications relative to the length of the distal extensions (cantilevers), and the satisfaction of the patients with a fixed implant-supported full-arch fiber-reinforced composites prosthesis.Materials and Method: A retrospective clinical and radiographic cohort study was developed. Clinical records of a selected cohort were analyzed according to inclusion and exclusion criteria. Data on a patient who underwent to fixed implant-supported full-arch fiber-reinforced composites prosthesis at least of five years of function were collected. Data analysis was performed using Kaplan-Meier curves and Fisher's Exact Test. P values less than 0.05 were considered statistically significant.Results: After insertion, 1 of 29 prostheses failed, the overall prosthetic survival rate observed at 5 years was 96.5%. Of the 120 implants placed in 28 patients, only 4 patients experienced loss of an implant during the 5 years of observation; the implant survival rate throughout the observation period was 86.2%. Distal extension seems to negatively affect the prognosis of implant-supported rehabilitation. Regarding the level of satisfaction of the patient with the prosthesis, none reported being uncomfortable or dissatisfied neither with their appearance nor with the taste of food throughout the studied period.Conclusion: No relevant associations were found between the variables involved. The study found the improvement in quality of life following the installation of fixed rehabilitation on the patients. Once the potential benefits of patients are obtained, controlled clinical trials are encouraged.